The triglyceride-glucose index trajectories are associated with cardiovascular diseases in people living with HIV: evidence from a prospective cohort study in China, 2005–2022 - Yinsong Luo; Liqin Sun; Yun He; Fang Zhao; Duo Shan; Fan Bu; Lingyun Ge; Xiaorui Li; Yiyao Hu; Xi Xiao; Hongzhou Lu; Jiaye Liu (BMC Public Health)
Abstract Background The triglyceride-glucose (TyG) index has been validated as a novel biomarker for cardiovascular disease (CVD) risk. However, the prospective relationship between baseline and long-term trajectories of the TyG index and CVD risk in people living with HIV (PLWH) remains unexplored. Methods This cohort study included 16,122 treatment-naive PLWH who initiated antiretroviral therapy (ART) at the Third People's Hospital of Shenzhen from 2005 to 2022. The TyG index was calculated as Ln [fasting triglycerides (mg/dL) × fasting glucose (mg/dL)/2]. Group-based trajectory modeling was used to identify distinct TyG index trajectories over the follow-up period. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using multivariate Cox proportional hazards models to assess the association between TyG index trajectories and CVD risk. Nonlinear relationships were investigated using a restricted cubic spline plot. Results During a median follow-up of 70 months, 214 PLWH developed CVD. Each 1-standard deviation (SD) increase in the baseline TyG index was associated with a 39% higher risk of CVD (HR 1.39, 95% CI 1.22, 1.59) after adjusting for covariates. Participants were categorized into four distinct TyG trajectory groups: low-stable, low-moderate-stable, high-moderate-stable, and high-increasing. After multivariate adjustment, the high-increasing trajectory group had a 2.92-fold (95% CI 1.68, 5.05) increased risk of CVD compared to the low-stable group. The restricted cubic spline plot showed an upward trend between the baseline TyG index and the CVD occurrence (P < 0.001), with the threshold at 8.479 for all HIV patients. Significantly positive correlations between the TyG index and CVD were observed both below the TyG threshold with HR 3.38 (95% CI 1.07, 10.68) and above the threshold with HR 1.43 (95% CI 1.07, 1.92) (both P < 0.05). After stratifying by sex, the spline curves in men were nearly identical to those observed in the overall HIV-infected population. While women also demonstrated a nonlinear association with a similar threshold (8.484), the relationship above the threshold was not statistically significant. Conclusions Higher baseline TyG index levels and the high-increasing trajectory were significantly associated with increased CVD risk in PLWH. These findings underscore the TyG index as a valuable marker for CVD risk assessment in PLWH, particularly in male populations. Incorporating TyG index monitoring into routine clinical assessments could enhance risk stratification and inform tailored prevention strategies. Further studies are needed to validate these findings in other cohorts and to explore their applicability in women.